Anxiety, Loneliness, Drug Craving, and Depression Among Substance Abusers in Sichuan Province, China - Chen, Xin; Qiu, Nan; Zhai, Liang; Ren, Gui (Frontiers in Pharmacology, 2021)
Objectives: In order to investigate the influence of anxiety on male drug addicts' depression as well as its inner mechanism-the mediating effect of loneliness and drug craving. Methods: State-Trait Anxiety Inventory, The UCLA Loneliness Scale, Drug Craving Scale, and The Center for Epidemiologic Studies Depression Scale were employed into this study to investigate 585 male drug addicts (age range of 20 to 58 years: M = 33.21, SD = 6.97). Results: The results indicated that: (1) Anxiety, loneliness, drug craving, and depression were significantly associated with each other. (2) Loneliness and drug craving mediated the link between anxiety and depression. Conclusions: In summary, the present study uncovered the mechanisms underlying the relation between anxiety on male drug addicts' depression, which had certain practical significance for preventing and intervening depression among male drug addicts.